The incidence and outcomes of acute coronary syndromes in a central European country: results of the CZECH-2 registry - Tousek, Petr; Tousek, Frantisek; Horak, David; Cervinka, Pavel; Rokyta, Richard; Pesl, Ladislav; Jarkovsky, Jiri; Widimsky, Petr; CZECH-2 Investigators (International journal of cardiology, 2014)
BACKGROUND: The incidence and treatment strategies of acute coronary syndrome (ACS) vary by region. Additionally, the clinical spectrum of ACS is changing and outcomes are improving. AIM: We assessed the incidence, treatment strategies, and outcomes of ACS for a well-defined population within a well-established network of percutaneous coronary intervention (PCI) centers and non-PCI centers. METHODS: The CZECH-2 registry included 1221 consecutive patients (mean age: 68 ± 13 years; 63.4% males) admitted for suspected ACS to 32 hospitals (including 4 PCI centers) within four Czech counties (total population: 2,370,841 inhabitants) during a 2-month period. RESULTS: The estimated incidence of confirmed ACS was 2,149 cases/million/year. In 374 (31%) patients, ACS was ruled out during the hospital stay. Coronary angiography (CAG) was performed in 60% of the patients overall and PCI was performed in 59% of the confirmed ACS patients. Killip classifications II-IV on admission were more common in patients with final diagnosis of non ST-elevation myocardial infarction (NSTEMI) than ST-elevation myocardial infarction (STEMI) (37.1% vs. 22.8%; p<0.001). The 30-day mortality rate was 5.7% for the whole study group, 7.3% for STEMI patients, 8.4% for NSTEMI patients, and 1.6% for patients with unstable angina pectoris (UAP), respectively. CONCLUSIONS: Almost one-third of the patients admitted for suspected ACS had a different final diagnosis. Among those with confirmed ACS, the use of CAG, PCI, CABG, and effective medications is rational. Outcome in NSTEMI patients was equivalent to those in STEMI patients, mainly due to the high-risk population in this group.
Keywords: Hospitals; výsledek terapie; Male; Percutaneous Coronary Intervention; Outcome; Risk Factors; mortalita v nemocnicích; Česká republika; akutní koronární syndrom; Acute coronary syndrome; nestabilní angina pectoris; Aged; mužské pohlaví; senioři; incidence; registrace; dostupnost zdravotnických služeb; infarkt myokardu; Hospital Mortality; Czech Republic; Treatment Outcome; Acute Coronary Syndrome; senioři nad 80 let; lidé; ženské pohlaví; Angina, Unstable; Humans; Registry; Myocardial Infarction; rizikové faktory; Aged, 80 and over; koronární angioplastika; Registries; Female; nemocnice; lidé středního věku; Incidence; Health Services Accessibility; Middle Aged